PERLINDUNGAN HUKUM TERHADAP BANK SELAKU KREDITUR SEPARATIS DALAM PERKARA PAILIT MELALUI PENDEKATAN TEORI HUKUM ALAM - Refra, Dirar Mahdirman; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Banks as separatist creditors holding mortgage rights are parties that should be outside the bankruptcy estate when a peron or legal enrtity is declared bankrupt. The bank as the holder of the mortgage is a creditor who long before the bankruptcy of a person or legal entity has been bound through an agreement with the person or legal entity that is bankrupt. The aim of this research is to understand and explore normatively the legal protection of banks as separatist creditors in bankruptcy cases. The research method uses normative juridical research, descriptive in nature, secondary data is analyzed qualitatively and conclusions are drawn using deductive logic. However, in practice the bank’s mortgage is in the hands of the curator, which means that the bank cannot execute it when the mortgage provider is unable to pay. This has resulted in banks as separatist creditors not getting adequate legal protection. The development progress achieved by a country, sepecially in the economic sector, cannot be separated from the role of bankin. This role is able to affect the pace of economic development in a country, one og whin is indonesia.  Keywords: Legal Protection, Bank, Bankruptcy